Geoffrey Hill's later work : radiance of apprehension - Wylie, Alex (Manchester University Press, 2019)
An exploration of the later work of Geoffrey Hill, often described as 'the greatest living poet' in his lifetime. This book reads, interprets, evaluates, and sets in context the work of Hill's prolific later period from 1996 to 2016, the year of his death.